Congenital cataracts – Clinical considerations in ultrasound diagnosis and management. Issue 1 (20th February 2020) - Thayalan, Krishanthy; Kothari, Anoushka; Khanna, Yash; Kothari, Alka
Abstract: Paediatric cataracts are one of the more common ocular abnormalities that occur in approximately 6 in 10, 000 infants and are a major cause of childhood blindness. A suggested pathological mechanism for congenital cataract formation is the abnormal arrangement of lens fibres during embryogenesis. While toxins, chromosomal abnormalities, infections and metabolic disorders account for the majority of the cases, up to 87% of unilateral cataracts remain idiopathic, making disease prevention an ongoing challenge. Early diagnosis and timely referral to ensure effective genetic counselling and postnatal follow‐up is paramount to prevent long‐term visual consequences. We describe three cases of congenital cataracts with incongruence in antenatal ultrasound findings and postnatal results. Improvement over time in the diagnostic sensitivity of ultrasound allows for early diagnosis of congenital cataracts, yet there is little published evidence regarding the sensitivity and specificity of ultrasound as a diagnostic modality. As congenital cataracts have significant long‐term implications if left untreated, such as loss of visual capacity and amblyopia, a targeted ultrasound survey should be performed at morphology scans, with a special focus on the orbital region. This should be extended to those with a significant family history of fetal eye abnormalities and severe malformations. Given the high proportion of idiopathic congenital cataracts, the scope of developing other preventative strategies is limited. Early and accurate diagnosis in the antenatal period may be feasible, by thorough examination of the eyes to detect ocular anomalies, especially in high‐risk individuals.